Multi-dimensional hydroxyapatite microspheres as a filling material of minicolumns for effective removal at trace level of noble and non-noble metals from aqueous solutions. Issue 2 (April 2018) - Silina, Yuliya E.; Koch, Marcus; Herbeck-Engel, Petra; Fink-Straube, Claudia
Graphical abstract: Highlights: The sorption interactions were determined by the concentration of H + in the influent. Co, Ni uptake at ammoniacal medium occurred via CoCa4 (PO4 )3 OH, NiCa4 (PO4 )3 OH formation. The sorption of Pb regardless from the pH was determined by Pb5-x Cax (PO4 )3 OH. The removal of noble metals was driven by in situ reduction to nanoparticles. Abstract: In this paper, the removal of noble and non-noble metals from aqueous solutions on multi-dimensional hydroxyapatite microspheres (MD-HAp-Ms) in column experiments was studied. The efficiency of non-noble metal removal, viz. Co(II) and Ni(II) commonly presented in the environment, and the attachment mechanism onto MD-HAp-Ms readily depended on the concentration of H + in the influent solution. In contrast, ICP-MS, SEM, XRD, TEM/EDX and RAMAN investigations independently revealed that the adsorption of Pb(II) onto the minicolumns was complete over the entire pH range and did not significantly depend on the medium acidity/basicity. The formation of a hydroxylpyromorphite phase with a general formula of Pb5-x /Cax (PO4 )3 OH onto the calcium MD-HAp-Ms minicolumns during Pb(II) uptake regardless from the used pH range was detected. Compared to non-noble metals, the noble ions Ag +, Pd 2+, Pt 2+, Au 3+ formed nanoparticles with an average size of 10–50 nm during adsorption onto the MD-HAp-Ms in ammoniacal medium. The efficiency of noble ions removal was in accordance with their standard electrode potential (E0 ).